1980
DOI: 10.1002/chin.198034167
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND ANTIVIRAL ACTIVITY OF HALOGENATED ADAMANTYLPHENOLS

Abstract: Ein bekanntes Antivirus‐Mittel ist das Tebrophen (I).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…19 It was readily synthesized by the alkylation of resorcinol with bromoadamantane without added catalyst. After recrystallization from toluene and drying at 120°C under vacuum, NMR indicated that solvent (0.5-2.0 wt %) was still present in the needles that were collected.…”
Section: Resultsmentioning
confidence: 99%
“…19 It was readily synthesized by the alkylation of resorcinol with bromoadamantane without added catalyst. After recrystallization from toluene and drying at 120°C under vacuum, NMR indicated that solvent (0.5-2.0 wt %) was still present in the needles that were collected.…”
Section: Resultsmentioning
confidence: 99%